2020
DOI: 10.1111/mec.15636
|View full text |Cite
|
Sign up to set email alerts
|

Seminal fluid protein divergence among populations exhibiting postmating prezygotic reproductive isolation

Abstract: Despite holding a central role in fertilization, reproductive traits often show elevated rates of evolution and diversification. The rapid evolution of seminal fluid proteins (Sfps) within populations is predicted to cause mis‐signalling between the male ejaculate and the female during and after mating resulting in postmating prezygotic (PMPZ) isolation between populations. Crosses between Drosophila montana populations show PMPZ isolation in the form of reduced fertilization success in both noncompetitive and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 98 publications
(219 reference statements)
1
21
0
Order By: Relevance
“…Ejaculate candidates with a signal peptide sequence showed elevated dN/dS ratios compared to the remaining ejaculate candidates (Mann-Whitney U test, p < 0.001 in all comparisons) and the genome average ( p < 0.006 in all comparisons), as expected for seminal fluid proteins (39, 42) (Fig. 3).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Ejaculate candidates with a signal peptide sequence showed elevated dN/dS ratios compared to the remaining ejaculate candidates (Mann-Whitney U test, p < 0.001 in all comparisons) and the genome average ( p < 0.006 in all comparisons), as expected for seminal fluid proteins (39, 42) (Fig. 3).…”
Section: Resultssupporting
confidence: 59%
“…Heterospecific ejaculates may fair worse in postcopulatory sexual selection (34, 35), have reduced motility (15, 36), or elicit an abnormal postmating female response, which can cause impaired sperm use or reduced oviposition rates (16, 20, 37, 38). A growing body of literature has begun characterising the genomic, transcriptomic, and proteomic differences between taxa that may contribute to postmating prezygotic isolation (16,20, 33, 3943).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMPZ isolation between Vancouver males and Colorado females is caused by the inability Vancouver males’ sperm to successfully fertilize Colorado females’ eggs [ 120 ], which could result from differences in male sperm length and female sperm storage organ morphology, interactions between sperm and egg cell surfaces and/or protein-level incompatibilities [ 18 ]. Interestingly, Garlovsky et al [ 122 ] identified more than 150 differentially abundant male ejaculate proteins between D. montana populations.…”
Section: The Evolution Of Reproductive Isolation (Ri) Between Diverging Lineagesmentioning
confidence: 99%
“…Cystatins are also a large and diverse group of genes, that regulate the activity of cysteine and serine proteases. Although little is known about their speci c functions in male reproductive tissues, cystatins have been found in seminal uids and reproductive tissues of ies, atworms and ticks (Garlovsky et al, 2020;Geadkaew et al, 2014;Sonenshine et al, 2011). They are thought to be involved in spermatogenesis and fertilization (Geadkaew et al, 2014), and have been found to play a critical role in regulating programmed cell death during embryogenesis in plants (P. Zhao et al, 2014) Secretory Genes Eighty percent (32) of AG genes analysed in S. punctum were secretory in nature, i.e., they synthesize secretory proteins (Figure 4d).…”
Section: Role Of Protease Inhibitors C-type Lectins and Cystatinsmentioning
confidence: 99%